Forgiveness, anger, and the limits of reciprocity: a critical note on Stephen Darwall’s the heart and its attitudes - Williges, Flavio; Vogelmann, Rafael (Voluntas: Revista Internacional de Filosofia, 2025)
This article provides a critical examination of Stephen Darwall’s The Heart and its Attitudes, where he extends his second-personal account of morality beyond deontic attitudes of the will to include non-deontic “attitudes of the heart”, such as love, trust, and forgiveness. Darwall argues that both domains share a common structure of reciprocity. While recognizing the significance of this contribution, we raise three main concerns. First, Darwall’s treatment of forgiveness risks reducing deontic forgiveness to a purely normative stance, leaving aside its affective dimension. Second, his account of “personal anger” tends to conflate anger with demands for recognition and care, thereby diluting its normative structure, widely recognized since Aristotle. Third, his general characterization of second-personal attitudes in terms of reciprocity obscures the role of personhood and moral authority in grounding presence, leaving unclear whether attitudes such as love for animals can be adequately described as second-personal. We conclude that although Darwall convincingly highlights the neglected moral importance of attitudes of the heart, his framework requires further clarification to remain faithful to the phenomenology of moral emotions and the conceptual foundations of second-personal relations.